(untitled) (Global Journal of Human-Social Science, 2023)
Traumatic brain injury is a health condition with high incidence morbidity and mortality that affects people of all ages considered a relevant public health problem around the world Trauma can greatly impact the lives of those affected from a socioeconomic point of view in dependence on third parties to carry out basic activities of daily living and social participation reflecting on the well-being and quality of life not only of survivors but also of their family members Quality of life and more recently human functionality are being used as important measures of health outcomes for the population and individuals The objective of this article is to discuss the repercussions of traumatic brain injury on the occupational performance and quality of life of post-trauma survivors in order to establish preventive and rehabilitative actions that minimize these impacts facilitate social reintegration and increase satisfaction with life of the affected subjects